Islamic Da’awah And Its Role In International Relations - Abdullahi , Auwal (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Islamic Da’wah plays a strategic role in shaping international relations through intercultural dialogue, the promotion of peace, and the strengthening of diplomatic ties among nations. This study addresses the problem of how Islamic Da’wah can effectively contribute to global diplomacy amidst challenges such as ideological conflicts, political manipulation, and media misrepresentation. The purpose of this research is to analyze Islamic Da’wah as an instrument of cultural and humanitarian diplomacy in building a just and peaceful global order. Using a qualitative method with a historical-normative approach, this study examines the contributions of Da’wah from classical to contemporary periods in the context of civilization, trade, and diplomacy. The findings reveal that Islamic Da’wah, grounded in the principles of wisdom (hikmah) and good counsel (maw‘idhah hasanah), promotes justice (‘adl), human dignity (karāmah insāniyyah), and humanitarian service (khidmat al-insāniyyah). Initiatives such as interfaith dialogue, humanitarian aid, and academic cooperation have proven effective in strengthening international relations and countering extremism. The key contribution of this study is to reframe Da’wah not merely as a religious endeavor, but as a form of soft diplomacy capable of bridging differences and fostering ethical global cooperation.